S50 Association of baseline blood eosinophil counts and serum IgE concentrations on exacerbations and benralizumab efficacy for patients with severe, uncontrolled asthma. (12th November 2019) - Jackson, DJ; Humbert, M; Hirsch, I; Newbold, P; Garcia Gil, E
Abstract : Introduction and objectives: Understanding the key drivers of exacerbations for patients with overlapping eosinophilic and allergic severe asthma is important for identifying the optimal treatment strategy. Benralizumab every 8 weeks (Q8W; first three doses every 4 weeks) decreases the annual asthma exacerbation rate (AAER) for patients with severe, uncontrolled asthma with baseline blood eosinophil counts (BBEC) ≥300 cells/µL and serum IgE concentrations ≥150 or <150 kU/L by 42% and 43%, respectively, vs. placebo ( Ann Allergy Asthma Immunol 2018;120:504–11). Our objectives were: 1) to determine the predictive value of serum IgE concentrations vs. BBEC on exacerbation risk for patients with overlapping eosinophilic and allergic asthma and 2) to evaluate benralizumab treatment effect for patients with eosinophilic asthma by baseline quartiles of serum IgE concentrations. Methods: For the first objective, pooled analyses of 1, 937 patients who received placebo in the benralizumab (Phase III SIROCCO and CALIMA and Phase IIb), tralokinumab (Phase III STRATOS 1 and 2 and Phase IIb), and tezepelumab (Phase II PATHWAY) exacerbation studies of approximately 1-year duration were performed. Crude AAER by BBEC and serum IgE concentrations were estimated for all patients and by atopy status. For the second objective, pooled analyses of SIROCCO and CALIMA patients receiving benralizumab 30 mg Q8W or placebo were performed. AAER was evaluated for overlapping BBEC and serum IgE concentrations via a negative binomial regression approach. Results: For the pooled placebo analysis, AAER increased with increasing BBEC but did not increase with increasing serum IgE concentrations (figure), which was also regardless of atopy status. For the pooled SIROCCO/CALIMA analysis population with BBEC ≥300 cells/μL, benralizumab resulted in similar improvements in AAER vs. placebo across all baseline serum IgE concentration quartile groups (figure). Similar results were observed for patients with BBEC ≥150 cells/μL. Conclusions: BBEC are important predictors of exacerbation risk. However, this was not observed with serum IgE concentrations. Patients with severe eosinophilic asthma treated with benralizumab had consistent reductions in the risk of exacerbations compared with placebo, regardless of serum IgE concentrations.